CUT DIAMETER OF CYCLONE SEPARATORS: PART I. MULTIPLE NONLINEAR REGRESSION - Demir, Selami; Karadeniz, Aykut; Ulutas, Kadir (YILDIZ TECHNICAL UNIV, 2020)
Pressure drop and particle collection efficiency are the two operating parameters for assessing the performance of cyclone separators. Although a great number of practical models exists for predicting the cyclone pressure drop in the design phase, models for estimating particle collection efficiency is very limited. In this study, an improved mathematical model for calculating cut diameter in cyclone separators, which is a measure of particle collection efficiency, was developed based on Lapple's formula. Modified Lapple's formula represents the cut diameters with R-2 = 0.9969 and relative mean square error (RMSE) of 2.533*10(-9). Also, a new empirical regression model was proposed (R-2 = 0.9619). The average errors of both models were very close to zero. Performance tests indicated that both models can be used confidently to predict cut diameter in cyclone separators.
Keywords: Cut diameter; cyclone separators; multiple nonlinear regression; particle collection efficiency; PRESSURE; PERFORMANCE; MODEL; Engineering